Pharmaceutical Care Berpengaruh terhadap Kualitas Hidup, Kepatuhan dan Outcome Klinis Pasien Diabetes Melitus Tipe 2 di Beberapa Daerah di Indonesia: Kajian Literatur - Salsabiella, Baiq Rani; Andanalusia, Mahacita (Fakultas Ilmu Kesehatan, 2025)
Diabetes mellitus is a metabolic disease in which there are abnormalities in insulin secretion, insulin action or both, causing hyperglycemia. Maximizing pharmaceutical services can be done as a step to improve the quality of life of diabetes mellitus patients and this can be done through pharmaceutical care by pharmacists. This literature review aims to determine the best interventions that can improve the quality of life, compliance and clinical outcomes of diabetes mellitus patients. This paper is the result of a literature review of various studies that examined the effect of pharmaceutical care on the quality of life, compliance and clinical outcomes of type 2 diabetes mellitus patients. A literature search was carried out via the Pubmed and Google Scholar websites using the keywords